THE IMPORTANCE OF INVESTMENT DECISIONS USING CAPITAL ASSET PRICING MODEL (CAPM) IN STOCK SECTOR TELECOMMUNICATION - Pristiwantiyasih, Pristiwantiyasih; Setyawan, Mochammad Ardi (STIE Mahardhika, 2020)
The purpose of this study is to analyze the overall performance of company shares in the telecommunications sector based on stock returns and risks, and determine the grouping and valuation of shares that are efficient and inefficient based on the Capital Asset Pricing Model (CAPM) method for companies in the telecommunications sector that listed on the Indonesia Stock Exchange (IDX) for the period 2015-2018. From the 4 shares of the research sample company, there were 3 shares that were considered efficient (undervalued). An undervalued stock is a stock that has an individual Return (Ri) greater than the expected rate of return [E (Ri)] and is above the Security Market Line (SML).